The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.physa.2018.11.042
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion behaviour of water confined in deformed carbon nanotubes

Abstract: We use molecular dynamics simulations to study the diffusion of water inside deformed carbon nanotubes with different degrees of eccentricity at 300K. We found a water structural transition between tubular-like to single-file for (7,7) nanotubes associated with change from a high to low mobility regimes. Water is frozen when confined in a perfect (9,9) nanotube and it becomes liquid if such a nanotube is deformed above a certain threshold. Water diffusion enhancement (suppression) is related to a reduction (in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 41 publications
3
33
0
1
Order By: Relevance
“…The formation of the more bonded system due to the increase in hydrogen bonds inside the nanotube decreases the diffusion of water through them. This is similar to the results reported by Mendonca et al [28]. As Feng et al [6] reported for the diffusion of helium gas through deformed nanotubes, the screw distortion did not have any significant impact on water transport, but the impact of the XY-distortion and Z-distortion were quite significant.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The formation of the more bonded system due to the increase in hydrogen bonds inside the nanotube decreases the diffusion of water through them. This is similar to the results reported by Mendonca et al [28]. As Feng et al [6] reported for the diffusion of helium gas through deformed nanotubes, the screw distortion did not have any significant impact on water transport, but the impact of the XY-distortion and Z-distortion were quite significant.…”
Section: Discussionsupporting
confidence: 91%
“…This shows that the formation of a more-bonded system decreases the water diffusion through the nanotubes. This is in good agreement with the results obtained by Mendonca et al [28]. This facilitates the change of diffusion from single file transport to near-Fickian diffusion.…”
Section: The Hydrogen Bondingsupporting
confidence: 93%
“…One outcome is an appreciation of the extraordinary complexity of the hydration patterns around an ion in the pore [18,22,29], as has been confirmed by numerous molecular dynamics (MD) simulations [5,8,22,30,31]. The latter reveal that the patterns are highly inhomogeneous, anisotropic and spatially clustered near membranes [32], inside nanotubes [33], and in nanoslits [16,34]. This clustering determines the distribution of charge around the ion, the local dielectric permittivity [35,36], and the strength of the ions' electrostatic interactions with their surroundings [37].…”
mentioning
confidence: 83%
“…Экспериментальное и теоретическое изучение углеродных нанотрубок, заполненных водой, показало, что молекулы воды могут заходить внутрь открытых нанотрубок и образовывать там протяженные цепочки водородных связей [7][8][9]. Механизмы транспорта протонов по таким цепочкам рассмотрены в работах [6,10].…”
Section: • • • O−h • • • O−h • • • O−h • • • выполняют роль протонных "unclassified